Cytotoxic, Antioxidant, and Caspase-9 activity of 2-(3,5-dibromo-4-methoxyphenyl)3(3-mercapto-5(pyridine-4-Yl)4H1,2,4-triazol-4yl)-thiazolidine4-one against various human tumor cell lines - Hassan, Firas A (Al-Nahrain Journal of Science, 2018)
Caspase, or cysteine-dependent aspartate-directed proteases, belong to a extremely protected group of cysteine proteases that have a crucial role within the numerous phases of apoptosis. The derivative of 2-(3,5-dibromo-4-methoxyphenyl)-3(3-mercapto-5(pyridine-4-yl)-4H1,2,4-triazol-4-yl)-thiazolidine4-one (C3) described a high toxic efficacy in murine melanoma tumor(B16F10), human prostate tumor (LCCaP), and non-small cell lung tumor (H1299) by measured half maximal inhibitory concentration IC50 values were 41 µg/ml, 54.11 µg/ml , and 109.9 µg/ml , respectively, which was the most significant cytotoxic towards (B16F10) cell line treated at (P<0.0001) for 24 hours. No significant cytotoxic effect were observed in human neuronal glioblastoma cell line (U138 MG) and testes cell lines (Tera-1) at P-value (0.650), by comparison with normal cell line. Furthermore, 1,2,4-Triazole derivative (C3) encouraged In-vitro increase in caspase-9 activity in (B16F10) tumor cell line. Derivative (C3) effect on the mechanism of apoptosis reveal a highly increased caspase-9 activity, which observed at 10 µg/ml concentrate in B16F10 cell line, IC50 was at 5.264 µg/ml. A series of 1,2,4-Triazole derivatives (C2, C3) were screened for their In -vitro antioxidant properties, through hydrogen peroxide, Nitric oxide, and total antioxidant capacity. The highest activity was indicated during measured (IC50, TAC50) values, with derivatives C2 and C3 by comparison with ascorbic acid as standard. Triazole derivative (C3) did not exhibit cytotoxic activity when applied human neuronal glioblastoma tumor (U138 MG) and testes cell line (Tera-1).